European company survey 2009 : Part-time work in Europe - Sander, Eszter (Luxembourg, 2011)
"Non-standard employment and, more particularly, part-time work has been increasing worldwide for the past two decades. This trend has been especially strong in Europe, where the issue of different working time arrangements is an important part of the discussion among policymakers and social partners, and something which the European Union (EU) has promoted to increase flexibility for workers and employers. However, part-time work is spread very unevenly across Member States, reflecting differences in legislation, infrastructure and cultural conventions. This report uses data from the fourth European Working Conditions Survey and the second Company Survey."